Birrul Walidain menurut Perspektif Hadis - Harneli; Irfan Saputra; Dedi Prayoga (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2023)
This study aims to explain how birrul walidain according to the hadith perspective. This research method uses a qualitative type through literature study by applying content analysis. The discussion of this research includes the meaning of birrul walidain (filial piety to parents), hadith of birrul walidain commands (filial piety to parents), forms of birrul walidain, and the virtues of birrul walidain (filial piety to parents). This study concludes that birrul walidain or filial piety to parents has a special position in Islamic teachings. The matter of filial piety to parents has been regulated both in the Quran and Hadith. According to the Hadith, filial piety is an obligation equal to faith, jihad, and taqwa. This research is expected to have benefits for the enrichment of the treasury of Islamic knowledge.